2021
DOI: 10.1016/j.heliyon.2021.e07158
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating pedagogical positions in higher education during COVID-19 pandemic: teacher's narratives

Abstract: Based on a qualitative semi-structured interview, this paper argues that pedagogical positions can be negotiated and adjusted once a policy is introduced and a safe space for negotiation is created. It is a case study where we cite evidence from a Saudi university that shows the change in teachers' assumptions and, consequently, the negotiation process they had gone through within their institution due to a sudden policy shift. The paper highlights the importance of policies and the surrounding circumstances w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 23 publications
(79 reference statements)
1
23
1
Order By: Relevance
“…Among the most frequent mental health disorders reported, the ones related to negative emotions such as anxiety, depression, stress, and distress stand out ( Browning et al., 2021 ; Fruehwirth et al., 2021 ; Hossain et al., 2021 ). The World Health Organization (WHO) exposes that dealing with telecommuting, home school, and lack of physical contact has demanded new adaptation skills for people to change their routines and reorganize their activities ( Alhawsawi and Jawhar, 2021 ). Moreover, psychological impacts of the pandemic in higher education students include increased cases of anxiety ( Wang et al., 2020 ), depression, eating disorders, alcohol and drug consumption ( Kohls et al., 2020 ), stress ( Van de Velde et al., 2020 ), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most frequent mental health disorders reported, the ones related to negative emotions such as anxiety, depression, stress, and distress stand out ( Browning et al., 2021 ; Fruehwirth et al., 2021 ; Hossain et al., 2021 ). The World Health Organization (WHO) exposes that dealing with telecommuting, home school, and lack of physical contact has demanded new adaptation skills for people to change their routines and reorganize their activities ( Alhawsawi and Jawhar, 2021 ). Moreover, psychological impacts of the pandemic in higher education students include increased cases of anxiety ( Wang et al., 2020 ), depression, eating disorders, alcohol and drug consumption ( Kohls et al., 2020 ), stress ( Van de Velde et al., 2020 ), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above results, the need for Computational Physics learning is a statement of challenges for each topic to arouse curiosity, learning resources other than textbooks provided by the lecturer, changes in strategies and methods as well as learning steps by lecturers and directions on how to make algorithms for solving Physics phenomena with computation, based on numerical analysis. Based on factor analysis,we found that the formulated as a factor model influenced the generative learning model with the cognitive conflict creative thinking orientation (GLCCSCTO) strategy in the Computational Physics course is 𝐹(𝑋) = 0.325𝑋 1 + 0.224𝑋 2 + 0.152𝑋 3 (4) where X1 is attitude towards Computational Physics, X2 is teaching materials and learning models, and X3 is learning style and creative thinking…”
Section: Discussionmentioning
confidence: 99%
“…Students' creative thinking is seen from how students create innovative ideas or projects when following and working on project assignments in the Computational Physics course. Nevertheless, institutional policies play an important role in shaping and reshaping lecturers' assumptions and practices when the following conditions are met with infrastructure and technology support, and ongoing training [4]. So, according to the opinion of students who want changes in strategies and methods as well as learning steps (changes in learning models).…”
Section: 24mentioning
confidence: 99%
See 1 more Smart Citation
“…During this certain condition, the courses of teaching-learning are conducted through the online-based platform. As stated by (Alhawsawi & Jawhar, 2021), this sort of teaching and learning may include bundled self-directed course material and learning exercises in a variety of LMSs, as well as interactive online sessions using a variety of technologies.…”
Section: Introductionmentioning
confidence: 99%